Formulasi wonton ikan patin (Pangius sp.) dan bayam hijau organik (Amaranthus hybridus l.) sebagai PMT pada balita gizi kurang di Puskesmas Tambakrejo - Putu Mahayani; Fitria Dhenok Palupi (UHAMKA PRESS, 2026)
Malnutrition is a condition characterized by inadequate nutrient intake, particularly energy and protein, which commonly affects children under five years of age. The direct causes of malnutrition include insufficient consumption of nutritious foods and the presence of infectious diseases. One potential nutritional intervention is the provision of supplementary food (PSF) based on locally available ingredients that are both acceptable and nutritionally adequate. This study developed PSF using patin fish and organic green spinach processed into dumplings as a high-protein alternative. This study aimed to determine the best formulation and analyze the sensory acceptability of dumplings made from patin fish and organic green spinach. An experimental study with a Completely Randomized Design (CRD) was conducted, consisting of one control group (F0) and three treatment groups (F1, F2, and F3) with varying proportions of ingredients. Organoleptic evaluation was conducted using a hedonic test involving 30 mothers of toddlers as untrained panelists. The assessment covered color, aroma, texture, and taste. The results showed that the F1 formulation achieved the highest average scores across all parameters, namely color (3.27), aroma (3.27), texture (3.27), and taste (3.53). The Kruskal-Wallis test indicated significant differences across all parameters (p<0.05). Further analysis using the Mann-Whitney test confirmed that F1 was significantly different from the other treatments. In conclusion, the best formulation was F1, containing 15 grams of patin fish and 10 grams of organic green spinach, which demonstrated the highest sensory acceptability and potential as a locally based supplementary food for toddlers.